Acute bacterial meningitis – challenges and conclusions - Cvetanovska, Marija; Grozdanovski, Krsto; Cana, Fadil; Demiri, Ilir; Spasovska, Katerina; Cvetanovski, Vlatko; Stojanoska, Tatjana; Milosavljevikj, Ane (IMAB Peytchinski Publishing Ltd., 2024)
Acute bacterial meningitis is an urgent condition characterized by significant morbidity and mortality. In the last decades, epidemiology of the most common etiologic agents as well as the age limit has changed significantly, with dominant involvement of the adult population and population at risk. Streptococcus pneumoniae remains the most common bacteria causing bacterial meningitis. The aim of this study is to observe the changes in the prevalence of etiologic agents and their dominance, the most commonly affected age groups, as well as comorbidities and complications in patients with acute bacterial meningitis treated at the University Clinic for Infectious Diseases in Skopje, R.N. Macedonia. In the last seven-year period, 194 patients with acute bacterial meningitis were treated. The etiologic agent in cerebrospinal fluid was confirmed in 94 (48.45%) patients, with the predominance of S. pneumoniae in 74 (78.72%). L. monocytogenes with 10 (10.63%) and N. meningitides with 6 (6.38%) were less represented. Male sex is dominant with 111 (57.21%) and older age groups as well. More than half of the patients, from the study, belonged to the at risk population with the highest percentage of them presenting with more than two comorbidities, as well as complications. In our study group, 41 (21.13%) of the patients died. Because of the substantial mortality and morbidity, it remains an urgent need to optimally deploy existing vaccines worldwide and develop new prevention strategies and treatment options.
Keywords: acute bacterial meningitis; S. Pneumoniae